By the Honourable Cadwallader Colden, Esq ; His Majesty's lieutenant governor, and commander in chief of the province of New-York ... A proclamation : Whereas it appearing that certain persons residing on or near the eastern boundaries of this province, had entered into a combination to dispossess Robert Livingston, Junior, Esq ; proprietor of the Manor of Livingston, in the colony of New-York, and the tenants holding under him ... Given under my hand and seal at arms, at Fort-George, in the city of New-York, the thirty-first day of March, 1762 . ([Printed by William Weyman], 1762)
Ordering the arrest of those making claim to Livingston Manor.